Perishable food supply chain quality (PFSCQ): A structured review and implications for future research. Issue 3 (2nd November 2015) - Siddh, Man Mohan; Soni, Gunjan; Jain, Rakesh
Abstract : Purpose: – The purpose of this paper is to provide a literature review of the perishable food supply chain quality (PFSCQ). It includes all the products/process from the farm to folk of perishable food (milk, meat, vegetable, grains and butter). Design/methodology/approach: – The methodology of a structured literature review involves selection of a representative sample of articles followed by classification of articles on the basis of research methodology and content of PFSCQ in the paper. Findings: – Research toward PFSCQ has risen in last five years. Fewer articles are addressing issues of developing countries then developed countries. Majority of the articles involved multiple as entity of analysis (combination of supplier, distributor, manufacturer, retailer and consumer), information as element of exchange and chain as the level of analysis. A large number of articles involved "agri-food, " "dairy" and "pork" as perishable products. Majority of articles used "case study" methodology. Statistical analysis as a tool for problem solving was used in majority of articles. Performance measurement aspect is also on growth in PFSCQ literature. Information sharing, logistic management, strategic management, demand forecasting and integration among the various stakeholders of PFSCQ are some of the critical issues. Originality/value: – Many literature reviews that aim at critical examination of supply chain literature are reported but none of them focussed exclusively on content of PFSCQ. Another unique feature of this paper is that the sample size of articles with respect to number of papers (481 papers) as well as number of journals (141 journals) is quite large. The paper spans a longer time span of 20 years (1994-2013) as well.